Co‐combustion of lignite with sewage sludge and refuse‐derived fuel - Ozfidan, Merve; Haykiri‐Acma, Hanzade; Yaman, Serdar (Wiley, 2019)
AbstractBurning behavior of fuel blends consisted of lignite samples and waste biomass species such as sewage sludge (SS) and refuse‐derived fuel (RDF) was studied. The blends where the wastes account for 5, 10, and 15 wt% were burned in a thermal analyzer up to 900°C. The nonisothermal burning kinetics were established using Borchardt and Daniels method that bases on the data obtained from differential scanning calorimetry. The maximum rate of combustion (Rmax), the peak temperature (TR‐max), the ignition temperature (Tign), and the burnout temperature (Tb) that predicts the thermal reactivity were considered to evaluate the effects of RDF and SS on the burning characteristics of the lignite samples. It was determined that the combinations of the additive behavior and the synergistic interactions govern the burning characteristics of the fuel blends. The thermal reactivity of the samples can be arranged in the order of RDF > lignite > SS. On the other hand, blending of RDF or SS with the lignite samples did not led to any significant segregation in the heat flow characteristics, and can be concluded that these wastes can be safely burned with lignite.